An inverted-sandwich diuranium μ-η5:η5-cyclo-P5 complex supported by U-P5 δ-bonding - Gardner, Benedict M.; Tuna, Floriana; McInnes, Eric J.L.; McMaster, Jonathan; Lewis, William; Blake, Alexander J.; Liddle, Stephen T. (Wiley-VCH Verlag, 2015)
Reaction of [U(TrenTIPS)] [1, TrenTIPS=N(CH2CH2NSiiPr3)3] with 0.25 equivalents of P4 reproducibly affords the unprecedented actinide inverted sandwich cyclo-P5 complex [{U(TrenTIPS)}2(μ-η5:η5-cyclo-P5)] (2). All prior examples of cyclo-P5 are stabilized by d-block metals, so 2 shows that cyclo-P5 does not require d-block ions to be prepared. Although cyclo-P5 is isolobal to cyclopentadienyl, which usually bonds to metals via σ- and π-interactions with minimal δ-bonding, theoretical calculations suggest the principal bonding in the U(P5)U unit is polarized δ-bonding. Surprisingly, the characterization data are overall consistent with charge transfer from uranium to the cyclo-P5 unit to give a cyclo-P5 charge state that approximates to a dianionic formulation. This is ascribed to the larger size and superior acceptor character of cyclo-P5 compared to cyclopentadienyl, the strongly reducing nature of uranium(III), and the availability of uranium δ-symmetry 5f orbitals.